2002
DOI: 10.1111/j.1365-2621.2002.tb10324.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Quality Index Method (QIM) Scheme in Shelf‐life Study of Farmed Atlantic Salmon (Salmo salar)

Abstract: Salmon (Salmo salar) was stored in ice up to 24 d, and changes during storage were observed with sensory evaluation using the Quality Index Method (QIM), and Quantitative Descriptive Analysis (QDA), total viable counts (TVC), hydrogen sulfide (H 2 S)-producing bacteria, and instrumental texture measurements (compression test). Maximum storage time in ice was determined with QDA and fat content by Soxhlet extraction. A high correlation between QIM and storage time in ice was found. Storage time could be predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
1
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 12 publications
9
91
1
7
Order By: Relevance
“…The pH in both AP and MAP fillets significantly decreases over the first 7 days, reaching minimal at pH 6.49 and 6.25, respectively (p<0.05). Similar results were reported by Cyprian et al [1], Erkan et al [3], and Sveinsdottir et al [13] reported that MAP fish with CO 2 showed increasing exudation of the CO 2 dissolved on the fish body surface mucus, resulting in muscle acidification and decreases in the pH. Therefore, pH in MAP was lower than that of AP during the storage.…”
Section: Physiochemical Effectssupporting
confidence: 84%
“…The pH in both AP and MAP fillets significantly decreases over the first 7 days, reaching minimal at pH 6.49 and 6.25, respectively (p<0.05). Similar results were reported by Cyprian et al [1], Erkan et al [3], and Sveinsdottir et al [13] reported that MAP fish with CO 2 showed increasing exudation of the CO 2 dissolved on the fish body surface mucus, resulting in muscle acidification and decreases in the pH. Therefore, pH in MAP was lower than that of AP during the storage.…”
Section: Physiochemical Effectssupporting
confidence: 84%
“…Judges were in better agreement when evaluating the fresh fish using the QI protocol, as compared to spoilage fish (Sveinsdóttir et al 2002). This was observed in the shelf-life study: the judges sensed the sensory changes caused by bacteria growth.…”
Section: Discussionmentioning
confidence: 54%
“…Penurunan mutu tersebut ditunjukkan oleh penurunan nilai organoleptik dari nilai awal 9 sesaat setelah ikan mati di atas kapal. Nilai organoleptik dan tekstur menurun selama penyimpanan dalam es (Andersen et al, 1995;Sveinsdottir et al, 2002). Green-Petterson et al, (2006) dan Farmer et al, (2000) melaporkan bahwa tidak hanya spesies tetapi juga perlakuan dan kondisi penyimpanan sangat berpengaruh terhadap karakteristik produk ikan.…”
Section: Teksturunclassified